The Wash-Out of Contrast-Enhanced Ultrasound for Evaluation of Hypoxic Ischemic Injury in Neonates and Infants: Preliminary Findings. Issue 1 (8th March 2022) - Sridharan, Anush; Riggs, Becky; Darge, Kassa; Huisman, Thierry A. G. M.; Hwang, Misun
Abstract: We evaluated the use of quantitative contrast-enhanced ultrasound (CEUS) to study wash-out behavior of ultrasound contrast agents in the pediatric brain in cases of hypoxic ischemic injury (HII). Six neonates and young infants were imaged using CEUS for suspected HII in the Neonatal Intensive Care Unit/Pediatric Intensive Care Unit. After receiving a bolus of ultrasound contrast agent Lumason (Bracco Diagnostics Inc.), analysis was performed in the whole brain, cortex, cortical/subcortical gray and white matter and central gray nuclei to quantify wash-out metrics and ratios. On magnetic resonance imaging clinical imaging findings, 3 children were classified as unaffected and 3 with classical imaging findings consistent with HII. A lower wash-out rate was found in the case of HII compared with the unaffected cases. Here, we present initial work exploring the wash-out behavior for differentiation between unaffected and HII in the brain. These preliminary findings are indicative of altered hemodynamics in HII and are promising for the potential use of CEUS to quantitatively differentiate between the unaffected and HII brain. Little is known about the CEUS wash-out dynamics, especially in the setting of the pediatric brain injury. Our preliminary findings are encouraging and warrant further investigation into the mechanisms behind delayed clearance of the ultrasound contrast agent in the setting of HII.